UMBILICAL CORD BLOOD BANKING (World Journal of Current Medical and Pharmaceutical Research, 2019)
Umbilical cord blood bank is a facility which stores umbilical cord blood for future use in both private and public cord banks. The banks which developed in response to the potential for cord blood in treatment for paediatric and adult patients presenting with haematological disorders, immunological defects and specific genetic diseases. The procedure which was used to collect the cord blood, storage and uses of the umbilical cord bank will be discussed in this article. Allergenic cord blood transplantation is of more than 25,000 performed worldwide since the first cord blood transplantation in 1988. More Than 7,80,000 cord blood units are stored in over 130 private cord blood banks, worldwide, and over 4,00,000 units in more than 100 quality controlled public cord banks. Umbilical cord banking is new way of curing the diseases researchers continue to evaluate the usefulness of cord blood cells in treating human diseases or disorders for purpose other than haematological disorders including heart disease, strokes, brain or spinal cord injuries and cancer. This review summarizes the status of potential use in the treatment of human disease.